THE ANALYSIS ON THE GRAMMATICAL ERRORS OF THE FIRST YEAR STUDENTS ESSAYS - . Sukarno (Soegijapranata Catholic University, 2016)
A language learner often faces many linguistic differences, especially if the native language and the target language are from different language families. The current study investigates the grammatical errors made by the first year students of the English Department, Faculty of Letters, Universitas Jember, Indonesia. The data were collected from 30 participants essays of Writing 01 class (documentary data) conducted from August to December 2014. Having been identified, the errors were classified into various categorizations, and analyzed based on descriptive-interpretative method to find the possible sources of the errors. The research revealed that the learners committed ten types of grammatical errors, and the six mostly prominent errors were plural form, subject-verb agreement, verb tense, word form, subject/verb omission, and passive voice respectively. This research also showed that the errors mostly resulted from the different linguistic principles of Indonesian and English (interlingual transfer), and partly from the faulty of overgeneralization of English rules (intralingual transfer). The overt influences of Indonesian to English as well as the overgeneralization of English rules can provide the writing teachers and course designers with insightful guidelines for better understanding of the sources of errors, which in turn, can help them to apply the more appropriate approaches to manage the foreign language learners errors of the year students